Handbook of best practice and standards for 2D+ and 3D imaging of natural history collections - Brecko, Jonathan; Mathys, Aurore (European Journal of Taxonomy, 2020)
Digitising a collection is key to make it last even after the physical objects are no longer available. Almost all of the techniques currently available to digitise a natural history collection in 2D+ and 3D are listed herein. The techniques are explained in a way that even one without any knowledge on the subject may understand their principle. The strong and weak points of the techniques are discussed, and an overview of suitable collections and specimens are given for each one of them. Also, plenty of examples already digitised with each technique are provided together with the links to visualise them in 3D. After explaining all the different digitisation options, the subsequent chapters provide information on how to improve the 2D+ and 3D digital twins of the specimens and techniques are compared to each other by means of test specimens. These give a fast overview of the capabilities of the digitisation techniques. Possible solutions to avoid digitisation errors are equally provided. Lastly, the dissemination of the results and the data management of the 3D models are briefly discussed in the final chapters. Also, a large chapter is provided with several workflows that can be followed to get the best possible results.